THE EFFECTIVENESS OF DIGITAL PLATFORMS IN DEVELOPING WRITTEN COMMUNICATION SKILLS IN JAPANESE LANGUAGE LEARNING (Web of Teachers: Inderscience Research, 2026)
This article analyzes the didactic potential of digital platforms in the process of developing written communication competence in the Japanese language. Within the framework of the study, the factors influencing the development of writing skills were identified, and the effectiveness of writing activities organized in a digital environment was evaluated. The results show that activities conducted through digital platforms significantly improve students’ grammatical accuracy, lexical activity, and text composition skills. In addition, an interactive learning environment has a positive impact on students’ independent thinking and writing performance.